2005
DOI: 10.1159/000093044
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Opioid Receptor Phosphorylation and Trafficking in Adaptations to Persistent Opioid Treatment

Abstract: µ-Opioid receptor activation underpins clinical analgesia and is the central event in the abuse of narcotics. Continued opioid use produces tolerance to the acute effects of the drug and adaptations that lead to physical and psychological dependence. Continued µ-receptor signaling provides the engine for these adaptations, with most evidence suggesting that chronic agonist treatment produces only limited alterations in primary µ-opioid receptor signaling. Here we examine agonist regulation of µ-opioid receptor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 93 publications
0
34
0
2
Order By: Relevance
“…with ␤-arrestins (Ferguson, 2001;Luttrell and Lefkowitz, 2002;Tohgo et al, 2003;Ahn et al, 2004;Prossnitz, 2004;Johnson et al, 2005;Lefkowitz et al, 2006;Marrari et al, 2007;Moore et al, 2007). The role of internalized heterotrimeric G proteins in vesicular trafficking has been recently recognized in yeast, in which it was demonstrated that endocytosis of G␣ is a required step in the signaling to Vps34, the yeast PI3K (Slessareva et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…with ␤-arrestins (Ferguson, 2001;Luttrell and Lefkowitz, 2002;Tohgo et al, 2003;Ahn et al, 2004;Prossnitz, 2004;Johnson et al, 2005;Lefkowitz et al, 2006;Marrari et al, 2007;Moore et al, 2007). The role of internalized heterotrimeric G proteins in vesicular trafficking has been recently recognized in yeast, in which it was demonstrated that endocytosis of G␣ is a required step in the signaling to Vps34, the yeast PI3K (Slessareva et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…It is known, however, that MOPRs are phosphorylated by multiple kinases (Johnson et al, 2005). Several kinase-dependent mechanisms have been proposed to mediate desensitization.…”
Section: Introductionmentioning
confidence: 99%
“…For example, biochemical assays for desensitization, such as inhibition of adenylyl cyclase that requires more than 5 minutes of sustained opioid exposure (most assays take 10-20 minutes, e.g., Law et al, 2000, or longer, e.g., Koch et al, 2005, measure the combined effects of rapid desensitization at the cell surface plus endocytosis or recovery from desensitization. Robust desensitization generally precedes endocytosis and can occur when endocytosis is absent or prevented (Johnson et al, 2005;Arttamangkul et al, 2006;Dang et al, 2009). While it is clear that arrestindependent internalization can sequester the opioid receptors in compartments that reduce the efficiencies of certain forms of signaling (e.g., Gbg activation of Kir3 channels), it is now equally clear that arrestin binding does not inactivate all receptor signaling.…”
mentioning
confidence: 99%